The Atlantic Zone of Costa Rica: agriculture in the Talamanca and Pococí/Guácimo study areas - Ee, S.B. van; Grundeman, M.P.; Hel, T.M. van de; Ottens, J.J. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
18 ref. Sum. (En)